The synergistic effect of carbon performance and technological innovation on corporate financial performance - Yan, Jin; Zhou, Hui; Mu, Jialin; Zhang, Ying; Rahman, Airin (Frontiers in Psychology, 2022)
In order to further implement the goal of "dual carbon" proposed by China’s government, and promote energy enterprises to carry out low-carbon economic transformation, this paper empirically studies the relations among carbon performance ,technological innovation and corporate financial performance in China's energy industry .We take listed firms in China's A-share energy industry from 2014 to 2019 as research samples. The results show that good carbon performance of the energy industry can positively affect financial performance of enterprises,which means that the better of carbon performance will promote the better of financial performance .We also find that technological innovation has significantly positively impact on energy firms’ financial performance . During the research of interactive relationship , we find that carbon performance and technological innovation have synergistic effect on energy firm's financial performance, which means technology innovation can significantly positive to adjust the action of carbon performance on financial performance ,and carbon performance at the same time can also be positive to adjust the action of technology innovation on financial performance. They mutually promote energy enterprise's financial performance. Further experimental research among different property- rights-owned enterprises ,we found that the synergistic effects of carbon performance and technological innovation on corporate financial performance is much more significant in non-state-owned enterprises, possibly due to private firms’ capital profit-seeking nature.The results will guide and inspire China’s energy enterprises’ low carbon development strategy formulation and implementation under the background of "dual carbon" goal .